Measuring the Implementation of Taxation Policy on Educational Services at State Universities as Legal Entities (PTN-BH) - Sari, Ade Rahma; Adiwarman, Adiwarman (Electronic Journal of Education, Social Economics and Technology, 2025)
Taxation policy plays a strategic role in supporting the education sector, especially in ensuring accessibility, governance efficiency, and equity of higher education. The application of Value Added Tax (VAT) on education services has undergone significant changes with the enactment of the Law on Harmonization of Tax Regulations (UU HPP), which changed the taxation scheme from exemption to tax exemption. This has an impact on the tax administration system at State Legal Entity Universities (PTN-BH), which are now required to issue tax invoices even though they do not pay VAT. In addition, the Income Tax (PPh) policy also plays a role in increasing the financial transparency of higher education institutions, especially in the implementation of the Article 21 Income Tax system that supports the principles of Good Corporate Governance (GCG). However, various challenges are still faced, including the uncertainty of tax regulations for PTN-BH, imbalances in tax incentive policies, and high administrative burdens for educational institutions. This study uses a literature review method to evaluate the impact of taxation policies on higher education, especially in the PTN-BH environment. The results of the study indicate that more adaptive tax policy reforms, more effective tax incentives, and a more transparent and efficient tax system are needed to support improving the quality of education in Indonesia. Therefore, optimizing tax policies for the education sector is a crucial step in creating a more inclusive and sustainable education system.